Focused visual attention distorts distance perception away from the attentional locus - Wardak, Claire; Denève, Sophie; Ben Hamed, Suliann (Neuropsychologia, 2011)
▶ Space is overestimated around the fixated position. ▶ Additional focused attention at the fixation position increases this overestimation. ▶ Attention-induced spatial overestimation is not specific to the locus of fixation. ▶ Rather, spatial distortion is centered around any locus of attention. ▶ This spatial distortion affects perception up to 8° away from the attentional locus. Several lines of evidence show that visual perception is altered at the locus of visual attention: detection is faster, performance better and spatial resolution increased. It is however not known whether attention can affect visual perception further away from its locus. In the present study, we specifically question whether and how visual attention influences spatial perception away from its locus, independently from any saccadic preparation. We use a landmark task in which subjects have to estimate the location of a bisection stimulus relative to two landmark stimuli 15° apart, while fixating one of them. This task is combined with a highly demanding discrimination task performed on one of the two landmarks. This allows us to test for the effect of spatial attention allocation on distance perception, as measured by the subject estimation of the landmarks midpoint. We show that the estimated midpoint is displaced towards the attentional locus, both when attention is instructed on the central landmark or on the peripheral landmark. These results suggest an overrepresentation of space around the attentional locus that can affect perception up to 8° away, and question the existence of an objective spatial representation. They are in line with reports of spatial distortion in hemineglect patients while they strikingly contrast with the spatial compression reported around the time of saccadic execution.